Grain growth and solid-state dewetting of Bi-Crystal Ni-Fe thin films on sapphire. (15th April 2019) - Sharma, Amit; Kumar, Aakash; Gazit, Nimrod; Srolovitz, David J.; Rabkin, Eugen
Abstract: We studied the solid-state dewetting behavior of thin Ni80 Fe20 films deposited on basal plane oriented sapphire substrate and annealed in the range of temperatures of 1023–1323 K. All studied films exhibited strong <111> texture and maze bicrystal microstructure, with only two grains misoriented by 60° around the common <111> axis present in the film. The morphology of partially dewetted films changed from the one typical for polycrystalline thin films to the one typical for single crystalline heteroepitaxial films with increasing temperatures and annealing times. This change of dewetting behavior was associated with the fast grain growth in the films. The films of pure Ni of identical thickness, annealed under identical conditions exhibited significantly slower grain growth and lower thermal stability. Both the high-resolution X-ray diffraction and the cross-sectional high-resolution transmission electron microscopy observations revealed the phase separation of the Ni80 Fe20 films into two parallel layers of the face-centered cubic (adjacent to the substrate) and hexagonal close-packed (on the top of the film) phases of similar compositions. Our density functional theory (DFT) calculations indicated that this phase separation is driven by the decrease of the film surface and interface energy, leading to the thermodynamically equilibrium thickness of the metastable hexagonal close-packed phase. This phase exhibits higher surface anisotropy than its stable face-centered cubic counterpart and is instrumental in accelerating the grain growth in the film via suppression of grain boundary grooving. Graphical abstract: Image 1